Acquisitions by Emerging Multinational Corporations Motivation and Performance of Transactions in Western Europe and North America - Distler, Johannes (Schriften zum europäischen Management, 2018)
This thesis analyzes the motivation and performance of 403 acquisitions made by emerging multinational corporations (EMNCs) in Western Europe and North America between 1994 and 2013. The findings indicate that most EMNCs were motivated to acquire in order to obtain access to the upstream and downstream know-how of their target firms. In addition, the thesis' event study results demonstrate that EMNCs on average generated value for their shareholders with their acquisitions over short periods around acquisition announcement. This result is particularly significant since similar studies on buying firms from developed markets have frequently come to the conclusion that acquirers destroy shareholder value. Contents Prior research on EMNCs and their M&A activity Event studies as a research method for measuring M&A performance Acquisition motivation and performance of EMNCs in Western Europe and North America Target Groups Researchers and students in international management with an interest in emerging multinational corporations Executives and advisors involved in M&A transactions of EMNCs The Author Dr. Johannes Distler completed his doctoral thesis under the supervision of Prof. Dr. Reinhard Meckl at the University of Bayreuth in Germany. He studied management at the University of Mannheim, University of St. Gallen, Kellogg School of Management and Pepperdine University, and works at an international consulting firm, advising clients on strategy, M&A and post-merger integration projects. .